Simulation of orographic precipitation’s component on the Mount Elbrus example - P. A. Toropov; A. A. Shestakova; J. I. Yarynich; S. S. Kutuzov (Лëд и снег)
A model of the orthographic component of precipitation based on the calculation of the condensation rate of water vapor in the air stream uplifting onto the mountain slope is proposed. The main assumptions of the model are: the cooling of the rising air is determined only by the adiabatic process; the orographic component of the vertical component of wind speed is generated by the relief, and its weakening with elevation is determined only by the atmospheric stratification; the proportion of precipitation from the total mass of the condensed moisture depends only on the air temperature. ERA5 reanalysis, which was previously compared with observational data, is used as initial data. The proposed model adequately reproduces the spatial and temporal variability of precipitation on the Elbrus slopes both for short episodes and on the climatic time scale (1985–2018). Comparison of the modeling results with the reconstruction of the annual accumulation of precipitation from the ice core obtained on the Western Elbrus Plateau in 2018 showed a statistically significant positive correlation. However, similar comparison with the data from the core extracted in 2009 did not give a statistically significant result. This means that the proposed model can be used as a tool for conformity between methods of accumulation reconstruction and for substantiation of their physical justification (correctness). In addition, this algorithm can be used to calculate monthly and annual sums of precipitation on mountain slopes of various exposures and to estimate annual accumulation on mountain glaciers.